Preliminarily phytochemical screening and in vivo safety evaluation of ethanolic extract of Hemidesmus indicus (Linn.) - Gita Mishra, Hemeshwer Kumar Chandra, Nisha Sahu, Satendra Kumar Nirala, Monika Bhadauria (Journal of Applied Pharmaceutical Science, 2018)
Objectives: Phytochemical and safety evaluation of Hemidesmus indicus (Linn.) of Apocynaceae family was performed to establish the justification of its therapeutic significance in traditional medicine. Material and Methods: Phytochemical analysis of leaf, stem, and root was done according to standardized protocols. For determination of no-observed-adverse-effect-level female rats were randomized into five groups of six animals, each administered with root extract at 100, 200, 400, and 800 mg/kg for 7 days. Blood was collected by a retro-orbital puncture for serum biochemical parameters. Choleretic activity was done by intra-duodenal administration of H. indicus root extract (400 mg/kg). Results: Hemidesmus indicus revealed the presence of alkaloids, flavonoids, tannins, saponins, terpenoids, carbohydrate, glycosides, proteins, flavonone, flavone, and flavonol, polyphenolic contents, and hydrogen peroxide scavenging activity. Root extract showed the highest amount of phytochemicals in comparison with leaf and stem. No significant difference was observed in alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase, bilirubin, albumin, urea, uric acid, creatinine, triglycerides, and cholesterol after treatments. The choleretic activity of H. indicus showed an insignificant upsurge in bile flow and bile solids. Conclusions: Hemidesmus indicus possesses phytochemicals responsible for its antioxidant and choleretic activity. Furthermore, administration of H. indicus root extracts up to 800 mg/kg is safe for in vivo studies in rats.
Keywords: Hemidesmus indicus,phytochemical analysis,NOAEL, choleretic activity.